2018
DOI: 10.3389/fnbeh.2018.00249
|View full text |Cite
|
Sign up to set email alerts
|

The Modulating Role of Sex and Anabolic-Androgenic Steroid Hormones in Cannabinoid Sensitivity

Abstract: Cannabis is the most commonly used illicit drug worldwide. Although its use is associated with multiple adverse health effects, including the risk of developing addiction, recreational and medical cannabis use is being increasing legalized. In addition, use of synthetic cannabinoid drugs is gaining considerable popularity and is associated with mass poisonings and occasional deaths. Delineating factors involved in cannabis use and addiction therefore becomes increasingly important. Similarly to other drugs of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 230 publications
(242 reference statements)
2
21
0
Order By: Relevance
“…The sex-dependent THC effects in time to right and open field, do however suggest that females may be more sensitive to the effects of THC at this time period. This finding is consistent with accumulating evidence demonstrating that sex is an important modulator of cannabinoid sensitivity resulting in a sexually dimorphic endocannabinoid system ( Struik et al , 2018 ). Overall however, we failed to support our hypothesis that THC prior to RmTBI conferred neuroprotection.…”
Section: Discussionsupporting
confidence: 92%
“…The sex-dependent THC effects in time to right and open field, do however suggest that females may be more sensitive to the effects of THC at this time period. This finding is consistent with accumulating evidence demonstrating that sex is an important modulator of cannabinoid sensitivity resulting in a sexually dimorphic endocannabinoid system ( Struik et al , 2018 ). Overall however, we failed to support our hypothesis that THC prior to RmTBI conferred neuroprotection.…”
Section: Discussionsupporting
confidence: 92%
“…It is actually possible that anabolic androgenic steroid use creates a vulnerability in the user to develop a dependence syndrome. Animal studies have highlighted the importance of sex hormones as modulators of drug sensitivity (Marusich, Craft, Lefever, & Wiley, ; Struik, Sanna, & Fattore, ). Chronic anabolic androgenic steroid use is understood to suppress the endocannabinoid system (Struik et al, ), with consequent reduction in reward function (Seitz et al, ; Wallin, Alves, & Wood, ).…”
Section: Motivators For Anabolic Androgenic Steroid Usementioning
confidence: 99%
“…Studies examining the neural regions of rats have reported greater CB1 receptor desensitization and downregulation in females, which may in part explain cannabis telescoping among females [33]. In addition, sex hormones may modulate cannabinoid sensitivity [34][35][36]. However, studies on the influence of sex hormones on responses to cannabinoids in humans are lacking [21].…”
Section: Cannabis Use Dependencementioning
confidence: 99%